2009
DOI: 10.1108/14635780910926658
|View full text |Cite
|
Sign up to set email alerts
|

Client influence on valuation: does language matter?

Abstract: PurposeThe purpose of this paper is to attempt to analyze client influence on valuation in both Taiwan and Singapore. Both countries are chosen because of the similar level of economic development as well as professionalism amongst valuers. However, although both are Chinese‐dominated by population, the culture and language used are substantially different.Design/methodology/approachThe study uses a survey questionnaire to sample valuers' response to client influence in both Taiwan and Singapore. The questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 9 publications
1
49
0
Order By: Relevance
“…Wolverton [34] has interpreted the positive impact of valuer affiliation with the firm offering consulting services on coercive client pressure as the result of probable internal conflicts of interest in these kinds of firms. A partly opposite conclusion can be drawn from the studies by Chen and Yu [41], in which the investigated valuers in Taiwan indicated that multiservice companies providing broader consultancy services are better at resisting client pressure. According to research by Liao, Chu, and Peng [43] in Taiwan, company size in practice weakens the independence of appraisals as a consequence of the pressure under which large appraisal companies perform.…”
Section: Previous Studiesmentioning
confidence: 80%
See 1 more Smart Citation
“…Wolverton [34] has interpreted the positive impact of valuer affiliation with the firm offering consulting services on coercive client pressure as the result of probable internal conflicts of interest in these kinds of firms. A partly opposite conclusion can be drawn from the studies by Chen and Yu [41], in which the investigated valuers in Taiwan indicated that multiservice companies providing broader consultancy services are better at resisting client pressure. According to research by Liao, Chu, and Peng [43] in Taiwan, company size in practice weakens the independence of appraisals as a consequence of the pressure under which large appraisal companies perform.…”
Section: Previous Studiesmentioning
confidence: 80%
“…They point at the client as a major party dictating the circumstances under which the property is valued. So far, studies verifying this belief have been conducted only in a few countries: New Zealand [28,29], the USA [9,[30][31][32][33][34][35], the UK [5,10,30,36,37], Nigeria [38][39][40], Singapore [41,42], Taiwan [41,43], and Malaysia [44]. To the best of our knowledge, there is only one published work (see [45]) relating to the impact of client pressure on Polish valuers; however, the survey method used to identify biased valuations seems debatable.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study showed that most appraisers' confidence in their valuations grew with greater access to information. Chen and Yu (2009) also found that as property appraisers' local knowledge and experience increased, so too did their confidence and ability to resist client influence. Lim et al (2006) found differences between the Chinese and Hong Kong territories in the use of information and in appraisal behaviour related to client influence and access to market information.…”
Section: Market Transparency: Geographical Differencesmentioning
confidence: 99%
“…Depending on the purpose of the appraisal (for use as collateral for obtaining credit or preparing annual accounts), clients may want a higher or lower estimate of the property's value. Previous research (Chen & Yu, 2009;Levy & Schuck, 1999 suggests that clients have 'information power' , meaning that their information can bias the appraisal. Levy and Schuck (2005) distinguish between information power and expert power as means of influence by defining information power as clients' control over information relevant to valuations and expert power as clients' expertise in property and the practice of valuation.…”
Section: First Decision: Information Sources To Usementioning
confidence: 99%
See 1 more Smart Citation